Optical genome mapping to decipher the chromosomal aberrations in families seeking for preconception genetic counseling - Kaili Yin; Mengmeng Li; Hanzhe Zhang; Jiazhen Chang; Qingwei Qi; Xiya Zhou; Jiangshan Guo; Yaru Wang; Xuequn Mao; Na Hao; Yulin Jiang (Scientific Reports)
Abstract Optical genome mapping (OGM) offers high consistency in simultaneously detecting structural and copy number variants. This study aimed to retrospectively evaluate the efficacy and potential applications of OGM in preconception genetic counseling. Herein, 74 samples from 37 families were included, and their results of OGM were compared to conventional methods, namely karyotyping (KT) and chromosomal microarray analysis (CMA), which identified 27 variants across 16 positive families. Notably, OGM achieved a concordance rate of 94.7% and 100% with KT and CMA, respectively, presenting an overall concordance of 96.3%, as it missed detecting a centromeric translocation. Additionally, OGM detected two cryptic balanced translocations and a small deletion in three families that were missed by conventional methods, improving the diagnostic rate by 5.4%, along with assisting in the diagnoses of six families (16.2%) by identifying complex rearrangements and confirming cryptic translocations. The combination of KT with OGM yielded the highest diagnostic rate in all families. Overall, the findings of this study present the notable potential of OGM for its application, combined with KT per requirement, in clinical settings to improve the efficiency and accuracy of diagnoses and rapid screening of individuals seeking preconception genetic counseling.